Financial Comfort Zone and the Academic Learning Ethos of KIP-Kuliah Scholarship Recipients: A Phenomenological Study in the Perspective of Islamic Values - A Mukhsin Irfangi; Pubita Sasti Fintani; Muhammad Hanif Abdillah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the effect of the financial comfort zone on the learning discipline of college students receiving the KIP-Kuliah scholarship. The financial comfort zone is a psychological condition where students feel secure due to full tuition coverage and monthly stipends, which potentially triggers a moral hazard in the form of academic passivity. This study employs a qualitative approach with a phenomenological method. Data were gathered through in-depth interviews and observation of KIP-Kuliah recipients whose class attendance fell below 75%. The results indicate that a stable financial comfort zone contributes to a decline in learning discipline when not accompanied by rigid institutional monitoring or strong intrinsic motivation. The guarantee of "free college" tends to diminish the students' sense of urgency, leading to behaviors such as skipping morning classes and delaying assignment submissions. This study recommends that higher education institutions implement a real-time attendance monitoring system directly tied to semesterly scholarship eligibility evaluations